2022
DOI: 10.1039/d2nj02827a
|View full text |Cite
|
Sign up to set email alerts
|

Tosyl/pyrrolyl-capped 1,3-enynes via t-BuOK-assisted reaction of TosMIC with acylethynylpyrroles: a new feature of this popular reagent

Abstract: 1-Tosyl-4-pyrrolyl-1,3-enynes have been synthesized in 37-68% yields by t-BuOK-assisted chemoselective reaction (reflux in THF, 1 h) of 2-(acylethynyl)pyrroles with tosylmethylisocyanide (TosMIC), a widespread reagent, which here manifests a new functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…At the same time, it was found that the reaction of 2-acylethynylpyrroles with TosMIC, depending on its conditions and substituents in the pyrrole ring, can deliver either pyrrolyl vinyl sulfones [ 40 ] or tosyl/pyrrolyl-capped 1,3-enynes [ 41 ]. In the former case, the reaction proceeds under a long reflux (120 h) in the Et 3 N/MeCN catalytic system, whereas for the easy and rapid (reflux, 1 h) synthesis of tosyl/pyrrolyl-capped 1,3-enynes, the t -BuOK/THF system is employed.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it was found that the reaction of 2-acylethynylpyrroles with TosMIC, depending on its conditions and substituents in the pyrrole ring, can deliver either pyrrolyl vinyl sulfones [ 40 ] or tosyl/pyrrolyl-capped 1,3-enynes [ 41 ]. In the former case, the reaction proceeds under a long reflux (120 h) in the Et 3 N/MeCN catalytic system, whereas for the easy and rapid (reflux, 1 h) synthesis of tosyl/pyrrolyl-capped 1,3-enynes, the t -BuOK/THF system is employed.…”
Section: Resultsmentioning
confidence: 99%